Caracterização e quantificação da população de fungos em área de produção de feno de capim Tifton 85, adubado com biofertilizante suíno - Macie, Liziane; Neres, Mufattoi Marcela Abbado; Nath, Caroline Daiane; Stangarlin, José Renato; Scheidt, Kácia Carine; Casarotto, Lidiane; Sarto, Jaqueline Rocha Wobeto [UNESP]; Sunahara, Samantha Mariana Monteiro (FapUNIFESP (SciELO), 2016)
The objective of this study was to quantify and identify the occurrence of the main genres of fungi soil, dead plant material, roots and shoots in Tifton 85 fertilized with swine biofertilizer, 7 days after start of regrowth. The evaluation were carried out during development (15, 22, 29 and 36 days of age) at the time of baling, hay and 30 days of storage. The experimental design was randomized blocks with split plots in time sub with 4 sampling sites (soil, plant tops, roots and dead plant material), and 6 times of evaluation for aerial part of the plant (15, 22, 29 and 36 days of regrowth, at the time of baling and 30 days of storage) and 4-cycle assessment for soil, roots and dead plant material (15, 22, 29 and 36 days of regrowth). In the counting and identification of genera of fungi belonging to each part of the plant and soil were averaged and those submitted to descriptive analysis. Greater fungal population was observed in soil and dead plant material, predominantly Penicillium in all parts of the plant studied.
Characterization and quantification of the population of fungi in area of tifton 85 bermudagrass hay fertilized with swine biofertilizer
Keywords: Cynodon spp; Hay; Organic manure; Sanitary quality